Telemedicine in patients with obsessive–compulsive disorder after deep brain stimulation: a case series - Wan, Xiaonan; Lin, Zhengyu; Zeng, Zhitong; Zhang, Yingying; Duan, Chengcheng; Zhang, Chencheng; Li, Dianyou (Frontiers in Human Neuroscience, 2024)
Background: Patients suffering from refractory obsessive-compulsive disorder (OCD) who have undergone deep brain stimulation (DBS) surgery require repeated in-person programming visits. These sessions could be labor-intensive and may not always be feasible, particularly when in-person hospital visits are restricted. Telemedicine is emerging as a potential supplementary tool for postoperative care.However, its reliability and feasibility still require further validation due to the unconventional methods of interaction.Method: A study was conducted on three patients with refractory OCD who had undergone DBS. Most of their programming sessions were completed via a remote programming system. These patients were recruited and monitored for a year. Changes in their clinical symptoms were assessed using the Yale-Brown Obsessive-Compulsive Scale-Second Edition (Y-BOCS-II), the Hamilton Anxiety Scale-14 (HAMA), the Hamilton Depression Scale-17 (HAMD), and the Short Form 36 Health Survey Questionnaire (SF-36). The scores from these assessments were reported.Results: At the last follow-up, two out of three patients were identified as responders, with their Y-BOCS-II scores improving by more than 35% (P1: 51%, P3: 42%). These patients also experienced some mood benefits. All patients observed a decrease in travel expenses during the study period. No severe adverse events were reported throughout the study.The group of patients showed improvement in their OCD symptoms within a one-year follow-up period after DBS surgery, without compromising safety or benefits. This suggests that telemedicine could be a valuable supplementary tool when in-person visits are limited.